Dynamic Response Analysis of FPSO With Damaged Mooring Line And Multiple Damaged Mooring Lines - Mohd Zahid, Muhammad Afiq Aiman (Universiti Teknologi PETRONAS, 2020)
Floating, Production, Storage and Offloading (FPSO) unit is a ship shaped vessel which is currently used worldwide for the production and storage of hydrocarbon in deep water region. FPSO is more economical and efficient compared to fixed structure. To install a fixed platform was more expensive since it need the stabilization and greater material strength capacity to withstand the amount of pressure exerted on the structure, therefore FPSO is preferable than fixed structure. FPSO is a floating structure that allow six degree of motion in surge, heave, sway, pitch, yaw and roll. The FPSO is stable due to the buoyancy design that been built during the ship design. However, it is crucial to study the dynamic response of FPSO and mooring system with damaged mooring line and damaged multiple mooring line for excellent station-keeping characteristic. Mooring line ensure the stability of the vessel itself and it keep the vessel in position during operation.